A Tunisian patient with CLCN2‐related leukoencephalopathy. Issue 12 (26th December 2022) - Ben Mohamed, Dina; Saied, Zacharia; Ben Sassi, Samia; Ben Said, Mariem; Nabli, Fatma; Achouri, Afef; Jeridi, Cyrine; Masmoudi, Saber; Amouri, Rim
Abstract: CLCN2‐related leukoencephalopathy (CC2L OMIM#: 615651) is a recently identified rare disorder. It is caused by autosomal recessive mutations in the CLCN2 gene and leads to the dysfunction of its encoded CLC‐2 chloride channel protein with characteristic brain MRI features of leukoencephalopathy. We report the first Tunisian patient with clinical features of ClCN‐2‐related leukoencephalopathy. A 54‐year‐old female with a family history of leukemia, male infertility, motor disability, and headaches who initially presented with a tension‐type headache and normal physical examination. At the follow‐up, she developed mild gait ataxia and psycho‐cognitive disturbances. A previously reported homozygous NM_004366.6(CLCN2):c.1709G > A (p.Trp570Ter) stop gained mutation was identified. This report expands the knowledge related to CC2L and highlights the clinical features in affected individuals of African descent. Abstract : Cerebral MRI axial T2‐weighted sequences (A–C) showing hyper T2 signal in the middle cerebellar peduncles (A), cerebral peduncles (B), and posterior limb of the internal capsule (C). Diffusion‐weighted sequences (D–F) showing hyperintensity in the middle cerebellar peduncles (D), cerebral peduncles (E), and posterior limb of the internal capsule (F). Apparent diffusion coefficient (ADC) map (G–I) does not show a restriction of diffusion.